Efeitos da simpaticotomia endoscópica sobre as artérias caróticas e vertebrais na terapêutica cirúrgica da hiperidrose primária - Cavalcante, Jeancarlo Fernandes (2005)
Analyze, in patients with primary hyperhidrosis (PH) who was undergone to videothoracoscopic sympathicotomy, the degree of vascular denervation after surgical transection of the thoracic sympathetic chain by measuring ultrasonografic parameters in carotid and vertebral arteries. Methods: Twenty-four patients with PH underwent forty-eight endoscopic thoracic sympathicotomy and were evaluated by duplex eco-doppler measuring systolic peak velocity (SPV), diastolic peak velocity (DPV), pulsatility index (PI) and resistivity index (RI) in bilateral common, internal and external carotids, besides bilateral vertebral arteries. The exams were performed before operations and a month later. Wilcoxon test was used to analyse the differences between the variables before and after the sympatholisis. Results: T3 sympathicotomy segment was the most frequent transection done (95,83%), as only ablation (25%) or in association with T4 (62,50%) or with T2 (8,33%). It was observed increase in RI and PI of the common carotid artery ( p<0,05). The DPV of internal carotid artery decreased in both sides (p<0,05). The SPV and the DPV of the right and left vertebral arteries also increased (p<0,05). Asymmetric findings were observed so that, arteries of the right side were the most frequently affected. Conclusions: Hemodynamic changes in vertebral and carotid arteries were observed after sympathicotomy for PH. SPV was the most often altered parameter, mostly in the right side arteries, meaning significant asymmetric changes in carotid and vertebral vessels. Therefore, the research findings deserve further investigations to observe if they have clinical inferences